Using the Five Ps: Conceptualizing COVID-19-Related Mental Health Concerns - Christine D. Gonzales-Wong; Scott Peters (Teaching and Supervision in Counseling, 2023)
The COVID-19 pandemic has resulted in rising mental health concerns. As individuals experience loneliness, anxiety, and depression related to the pandemic, counselors-in-training navigate their treatment of clients while also living through the pandemic and its polarization. The authors present the Five Ps, a case conceptualization model that supervisors can use to help beginning counselors consider the history and context of the presenting concerns of clients, in addition to utilizing clients’ strengths in treatment. The authors provide a case illustration using the Five Ps in a supervision setting and discuss implications for supervision and future research.
Keywords: case conceptualization; loneliness; pandemic; supervision